Evolution of Structural Diversity of Triterpenoids - Cárdenas, Pablo D.; Almeida, Aldo; Bak, Søren (Frontiers in Plant Science, 2019)
Plants have evolved to produce a blend of specialized metabolites that serve functional roles in plant adaptation. Among them, triterpenoids are one of the largest subclasses of such specialized metabolites, with more than 14,000 known structures. They play a role in plant defense and development and have potential applications within food and pharma. Triterpenoids are cyclized from oxidized squalene precursors by oxidosqualene cyclases, creating more than 100 different cyclical triterpene scaffolds. This limited number of scaffolds is the first step towards creating the vast structural diversity of triterpenoids followed by extensive diversification, in particular, by oxygenation and glycosylation. Gene duplication, divergence, and selection are major forces that drive triterpenoid structural diversification. The triterpenoid biosynthetic genes can be organized in non-homologous gene clusters, such as in Avena spp., Cucurbitaceae and Solanum spp., or scattered along plant chromosomes as in Barbarea vulgaris. Paralogous genes organized as tandem repeats reflect the extended gene duplication activities in the evolutionary history of the triterpenoid saponin pathways, as seen in B. vulgaris. We review and discuss examples of convergent and divergent evolution in triterpenoid biosynthesis, and the apparent mechanisms occurring in plants that drive their increasing structural diversity within and across species. Using B. vulgaris’ saponins as examples, we discuss the impact a single structural modification can have on the structure of a triterpenoid and how this affect its biological properties. These examples provide insight into how plants continuously evolve their specialized metabolome, opening the way to study uncharacterized triterpenoid biosynthetic pathways.